Indoleamine 2,3-dioxygenase-expressing mature human monocyte-derived dendritic cells expand potent autologous regulatory T cells - Chung, David J; Rossi, Marco; Romano, Emanuela; Ghith, Jennifer; Yuan, Jianda; Munn, David H; Young, James W (Blood, 2009)
A comprehensive understanding of the complex, autologous cellular interactions and regulatory mechanisms that occur during normal dendritic cell (DC)-stimulated immune responses is critical to optimizing DC-based immunotherapy. We have found that mature, immunogenic human monocyte-derived DCs (moDCs) up-regulate the immune-inhibitory enzyme, indoleamine 2,3-dioxygenase (IDO). Under stringent autologous culture conditions without exogenous cytokines, mature moDCs expand regulatory T cells (Tregs) by an IDO-dependent mechanism. The priming of resting T cells with autologous, IDO-expressing, mature moDCs results in up to 10-fold expansion of CD4(+)CD25(bright)Foxp3(+)CD127(neg) Tregs. Treg expansion requires moDC contact, CD80/CD86 ligation, and endogenous interleukin-2. Cytofluorographically sorted CD4(+) CD25(bright)Foxp3(+) Tregs inhibit as much as 80% to 90% of DC-stimulated autologous and allogeneic T-cell proliferation, in a dose-dependent manner at Treg:T-cell ratios of 1:1, 1:5, and as low as 1:25. CD4(+)CD25(bright)Foxp3(+) Tregs also suppress the generation of cytotoxic T lymphocytes specific for the Wilms tumor antigen 1, resulting in more than an 80% decrease in specific target cell lysis. Suppression by Tregs is both contact-dependent and transforming growth factor-beta-mediated. Although mature moDCs can generate Tregs by this IDO-dependent mechanism to limit otherwise unrestrained immune responses, inhibition of this counter-regulatory pathway should also prove useful in sustaining responses stimulated by DC-based immunotherapy.